Pengharmonisasian, Pembulatan, dan Pemantapan Konsepsi Rancangan Peraturan Daerah Tugas dan Fungsi Kementerian pada Pasal 99A Undang- Undang Nomor 12 Tahun 2011 Tentang Pembentukan Peraturan Perundang- Undangan No. Undang-Undang Nomor 15 Tahun 2019 - Winajat Winajat; Syahrul Borman; Dudik Jaya Sidharta (Lembaga Pengembangan Kinerja Dosen, 2025)
Law Number 15 of 2019 in Article 58, Article 85 and Article 91 contains authority that must be carried out by ministries or institutions that carry out government affairs in the field of Legislation Formation. Until early 2025, the government has not formed the ministry or institution in question. The legal issue of this normative legal research: What is the form of regulation of harmonization, rounding, and consolidation of the conception of the Draft Regional Regulation? What is the authority of the ministry in harmonizing, rounding, and consolidating the conception of the Draft Regional Regulation? The arrangement of harmonizing, rounding, and consolidating the conception of the Draft Regional Regulation involves a series of steps that are structured and regulated by laws and regulations. Harmonization is the process of harmonizing and unifying draft regulations so that there is no conflict with existing regulations. Coordination, For the Draft Regional Regulations that come from the Regional People's Representative Council, harmonization is coordinated by the fittings of the Regional People's Representative Council that handles the field of legislation. The authority of the ministry in harmonizing, rounding, and consolidating the conception of the Draft Regional Regulation is rooted in Article 18 paragraph (6) of the 1945 Constitution which states that local governments have the right to establish regional regulations, which are the implementation of regional autonomy. Article 236 of Law Number 23 of 2014 emphasizes that regional regulations must be prepared as an elaboration of higher laws and regulations. Since the promulgation of Law Number 15 of 2019, there has been a significant change in the authority to harmonize the Draft Regional Regulations.